The Effect of Platinum Derivatives on MDA-MB-231 and MCF7 Breast Cancer Cell Lines Viability and the Role of the ABCs and CSCs in Chemoresistance - سكرية, شادي; مراد, حسام; الغميان, يمان (Latakia University Journal -Medical Sciences Series, 2021)
Breast cancers are the leading cause of death in women worldwide. Breast cancers are heterogeneous at the molecular level and in their response to chemotherapy. Chemoresistant is an essential reason for treatment failure and the high mortality. Emerging evidence associate ABCs expression, cancer stem cells and acquisition of chemoresistance in cancer. Here we investigate the response of MDA-MB-231 and MCF7 cell lines to cisplatin and carboplatin and we determine the role of the previous mechanisms in resistance at the molecular level. This research was conducted in the human cancer cells laboratory of the Atomic Energy Commission from the beginning of 2018 to 7th of 2020. MCF7 and MDA-MB-231 breast cancer cell lines were purchased from the British Cancer Cell Bank. MDA-MB-231 and MCF7 cells were treated with increased concentrations of cisplatin and carboplatin. Cell viability was determined by XTT. Gene expression of the most important members of the ABC family; ABCB1, ABCC1, ABCC2 and ABCC3 and the breast cancer stem cells markers CD44, CD24, ALDH1 were studied with Real time PCR. Our results indicated that cisplatin and carboplatin treatments reduced the cell viability for both studied lines. MDA-MB-231 line was more resistant to cisplatin and carboplatin. MDA-MB-231 cisplatin resistant fold increased 6 times compared to MCF7 line. Our results showed that cisplatin reduced MDA-MB-231 and MCF7 viability more than treatment with carboplatin. The expression of ABCB1, ABCC1, ABCC2, and ABCC3 genes, decreased 0.05, 0.02, 0.3, and 0.05 times, respectively in MDA-MB-231 cells compared to MCF7 cells. MDA-MB-231 cells also had a high expression of the stem cells marker ALDH1 (46.9 times) compared to MCF7 cells.